Teacher Well-Being and Perceived School Climate during COVID-19 School Closure: The Case of Physical Education in Switzerland. Issue 1 (2nd January 2022) - Cece, Valérian; Guillet-Descas, Emma; Lentillon-Kaestner, Vanessa
Abstract: School closure and distance learning during the COVID-19 lockdown had the potential to affect teachers' perception of their well-being and of the school climate. Within the teaching community, physical education (PE) teachers particularly redesigned their activities during school closures, posing both opportunities and threats. The study aim was to contribute to the understanding of the teachers' well-being experiences (burnout and engagement) and school climate perceptions during the lockdown for PE teachers in comparison with those of teachers of other subjects. The results from 188 teacher questionnaire responses revealed better psychological experiences among PE teachers in 2020 compared to those in a traditional year and compared to those of teachers of other subjects. School closure was related to higher collaboration, vigor scores and lower levels of physical fatigue for PE teachers. These positive effects for the PE teachers suggest using some profits of the COVID-19 period in normal teaching conditions